2013
DOI: 10.1002/asia.201300078
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of CuO Nanoplates into Porous Hybrid Cu2O/Polypyrrole Nanoflakes through a Pyrrole‐Induced Reductive Transformation Reaction

Abstract: Porous hybrid Cu2O/polypyrrole nanoflakes have been synthesized from solid CuO nanoplate templates through the pyrrole-induced reductive transformation reaction at elevated temperature. The conversion mechanism involves the reductive transformation of CuO to Cu2O and the in situ oxidative polymerization of pyrrole to polypyrrole. In addition, the morphology of the as-converted nanohybrids depends on the shape of the CuO precursors. The strategy enables us to transform single-crystalline CuO nanosheets into hol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 102 publications
0
27
0
Order By: Relevance
“…It has been widely proved that the conducting polymer coating is an efficient approach to improving the electron transport in electrodes because of their easy and environmental processability as well as superior electrical properties. [22,23] Of particular interest, it was found that polymerization of pyrrole monomers lead to the simultaneous reduction of Fe 2 O 3 and PPy coating process, resulting in the successful formation of hierarchical nanocages of Fe 3 O 4 @PPy. By using as-prepared hierarchical Fe 3 O 4 @PPy nanocages as the anode, it was demonstrated that they exhibited excellent electrochemical performances, such as improved large reversible capacity, rate capability, and long-term cycling stability.…”
Section: Doi: 101002/aenm201600256mentioning
confidence: 99%
“…It has been widely proved that the conducting polymer coating is an efficient approach to improving the electron transport in electrodes because of their easy and environmental processability as well as superior electrical properties. [22,23] Of particular interest, it was found that polymerization of pyrrole monomers lead to the simultaneous reduction of Fe 2 O 3 and PPy coating process, resulting in the successful formation of hierarchical nanocages of Fe 3 O 4 @PPy. By using as-prepared hierarchical Fe 3 O 4 @PPy nanocages as the anode, it was demonstrated that they exhibited excellent electrochemical performances, such as improved large reversible capacity, rate capability, and long-term cycling stability.…”
Section: Doi: 101002/aenm201600256mentioning
confidence: 99%
“…In the present communication, we propose Cu x O voltage cycling redox efficiency improvement through its coating with protective/catalyst layer of a transparent wide-gap semiconductor (either ZnO or TiO 2 ). Some recent dated studies showed that porous hybrid Cu 2 O/polypyrrole nanostructures exhibited efficient catalytic activity toward oxygen reduction reaction (ORR), thus making them promising nonprecious-metal-based catalysts for ORR in alkaline fuel cells and metal-air batteries [19].…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] Because of their high cost, lower abundance, low stability and sluggish kinetics Pt based electrocatalysts, which are currently the best electrocatalyst for ORR, many research groups are attempting to find non-precious metal electrocatalysts, such as non-precious metals themselves, [5][6][7][8][9][10][11][12][13] their alloys, metal oxides, 14 metal nitrides, 15,16 metal oxynitrides, 17,18 metal carbides 16,19 as well as N-and B-doped carbon materials with and without metal doping. [1][2][3][4] Because of their high cost, lower abundance, low stability and sluggish kinetics Pt based electrocatalysts, which are currently the best electrocatalyst for ORR, many research groups are attempting to find non-precious metal electrocatalysts, such as non-precious metals themselves, [5][6][7][8][9][10][11][12][13] their alloys, metal oxides, 14 metal nitrides, 15,16 metal oxynitrides, 17,18 metal carbides 16,19 as well as N-and B-doped carbon materials with and without metal doping.…”
Section: Introductionmentioning
confidence: 99%